Climate-Smart Village approach mainstreamed in the Philippines, Vietnam, Myanmar, Laos, and Cambodia - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
The CSV approach has been mainstreamed in national programs in the Philippines and Vietnam, and in new projects in Myanmar, Laos, and Cambodia. To date, the CSV approach has been used in 33 sites.